Persistence of transferred fragrance on fabrics for forensic reconstruction applications. Issue 1 (January 2020) - Gherghel, Simona; Morgan, Ruth M.; Arrebola-Liébanas, Javier F.; Blackman, Chris S.; Garrido-Frenich, Antonia; Parkin, Ivan P.
Abstract: It has recently been established that volatile organic compounds (VOCs) successfully transfer between clothing even with a short contact of 10 s, highlighting the potential to use VOCs in forensic reconstruction scenarios, such as sexual assault cases. The mid and low volatility compounds transferred in greater amounts than high volatility compounds. This study presents empirical data addressing the persistence of transferred VOCs on clothing for the first time. A series of experiments were carried out to determine the persistence of VOCs on clothing for time periods of up 4 weeks, on natural and synthetic fibres, and at three different environmental temperatures. The data indicate that the highest VOC amounts are generally obtained for shorter persistence times of up to 1 d. Whilst high volatility compounds were not recovered in sufficient amounts to allow quantification, the four other transferred VOCs were successfully quantified for persistence times of up to 4 weeks. The persistence for mid-volatility compounds follows decay curve trends in line with those previously obtained for fibres, glass and pollen. When comparing the persistence of VOCs on a natural and a synthetic fibre, for a persistence time of 1 h, the transferred VOCs were retained on a natural fibre in higher amounts than on a synthetic fibre. However, for longer persistence times the concentration of VOCs was similar between the two fabrics. Lastly, lower environmental temperatures resulted in higher recoveries for most VOCs, especially for short persistence times. These findings demonstrate that optimal recovery of VOCs from clothing occurs when the fabric is kept at cooler temperatures and analysed soon after the fragrance transfer occurred, although VOC recovery was possible at higher temperatures and after longer persistence times. Given the transfer and persistence characteristics of VOCs from fragrance, there is potential for fragrance to be used as a form of trace in forensic reconstruction approaches. Highlights: Transferred fragrance can persist on clothing for as long as 4 weeks. Highest VOC amounts were obtained for shorter persistence times of up to 1 day. Similar amounts of VOCs were recovered from a natural and a synthetic fibre. Storage in a freezer offered greater levels of VOC recovery. Fragrance as a form of trace evidence shows potential for forensic reconstructions.